ChemInform Abstract: Synthesis of Enantioenriched 1, 2‐trans‐Diamines Using the Borono‐Mannich Reaction with N‐Protected α‐Amino Aldehydes. Issue 42 (October 2015) - Norsikian, Stephanie; Beretta, Margaux; Cannillo, Alexandre; Martin, Amelie; Retailleau, Pascal; Beau, Jean‐Marie
Abstract 1, 2‐trans‐diamines are prepared with an enantiomeric excess of up to 98% e.e.